2022
DOI: 10.3390/cimb44100349
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Selection of a CFTR Modulator for a Patient with a Complex Allele [L467F;F508del]

Abstract: The presence of complex alleles in the CFTR gene can lead to difficulties in diagnosing cystic fibrosis and cause resistance to therapy with CFTR modulators. Tezacaftor/ivacaftor therapy for 8 months in a patient with the initially established F508del/F508del genotype did not lead to an improvement in her condition—there was no change in spirometry and an increase in the patient’s weight, while there was only a slight decrease in NaCl values, measured by a sweat test. The intestinal current measurements of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Thus, to address this unresolved issue, researchers have characterized the association between CFTR genotype, phenotype and its modulation by ELX/TEZ/IVA in recombinant cells ( Laselva et al, 2021 ; Borgo et al, 2022 ; Tomati et al, 2022 ) or patient-derived epithelial cells in vitro ( Veit et al, 2021b ; Borgo et al, 2022 ; Shaughnessy et al, 2022b ; Furstova et al, 2022 ; Tomati et al, 2022 ). Alternatively, they combined the cell culture work with the examination of CFTR biomarkers and clinical characteristics prior and during treatment with ELX/TEZ/IVA ( Anderson et al, 2021 ; Comegna et al, 2021 ; Huang et al, 2021 ; Terlizzi et al, 2021 ; Aalbers et al, 2022 ; Kondratyeva et al, 2022a ; 2022b ; Ciciriello et al, 2022 ; Sondo et al, 2022 ). A peculiar challenge are complex alleles not yet documented in the databases.…”
Section: Exposure Of Elx/tez/iva To Rare Cftr Geno...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, to address this unresolved issue, researchers have characterized the association between CFTR genotype, phenotype and its modulation by ELX/TEZ/IVA in recombinant cells ( Laselva et al, 2021 ; Borgo et al, 2022 ; Tomati et al, 2022 ) or patient-derived epithelial cells in vitro ( Veit et al, 2021b ; Borgo et al, 2022 ; Shaughnessy et al, 2022b ; Furstova et al, 2022 ; Tomati et al, 2022 ). Alternatively, they combined the cell culture work with the examination of CFTR biomarkers and clinical characteristics prior and during treatment with ELX/TEZ/IVA ( Anderson et al, 2021 ; Comegna et al, 2021 ; Huang et al, 2021 ; Terlizzi et al, 2021 ; Aalbers et al, 2022 ; Kondratyeva et al, 2022a ; 2022b ; Ciciriello et al, 2022 ; Sondo et al, 2022 ). A peculiar challenge are complex alleles not yet documented in the databases.…”
Section: Exposure Of Elx/tez/iva To Rare Cftr Geno...mentioning
confidence: 99%
“…A peculiar challenge are complex alleles not yet documented in the databases. Characterization of p.[Leu467Phe-Phe508del] in patient-derived organoids and primary intestinal epithelium demonstrated a more compromised CFTR function than p.Phe508del, but fortunately was susceptible to modulation by ELX/TEZ/IVA both in vitro and in the patient in vivo ( Kondratyeva et al, 2022a ; Kondratyeva et al, 2022b ).…”
Section: Exposure Of Elx/tez/iva To Rare Cftr Geno...mentioning
confidence: 99%
“…At the same time, the clinical course of the disease in groups with genotypes p.Phe508del/p. [Leu467Phe;Phe508del] and p.Phe508del/p.Phe508del did not differ in age of diagnosis, characteristics of respiratory function, nutritional and microbiological status, frequency of exacerbations, or therapy, including courses of intravenous antibacterial therapy [ 20 , 21 ].…”
Section: Regional Prevalence Of Complex Allelesmentioning
confidence: 99%
“…Previously, it was found that the p.Leu467Phe variant does not lead to the development of CF, but reduces the amount of functional (fully glycosylated) CFTR by two times compared to the norm [ 55 ], but p.Leu467Phe in combination with p.Phe508del causes a lack of response to treatment with CFTR correctors [ 20 ]. Variants of p.Leu467Phe and p.Phe508del have an additive pathogenic effect, which can no longer be eliminated by the lumacaftor corrector.…”
Section: Effectiveness Of Targeted Therapy In Patients With Complex A...mentioning
confidence: 99%
See 1 more Smart Citation